PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Sendyanto , Sendyanto; Tjhai, Fung Njit (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to examine the effect of the independent variables of leverage, firm size, size of a public accounting firm, profitability, audit committee, institutional ownership, and sales growth on the dependent variable tax avoidance. The population used in this study were all manufacturing companies listed on the Indonesian Stock Exchange (IDX). The sample selection method used a purposive sampling method, where in this study obtained 66 manufacturing companies during the 2019-2021 period that met the criteria so that the data used as a sample for this study amounted to 198 sample data. The data used in this study is secondary data sourced from the Indonesian Stock Exchange website. To test each independent variable on tax avoidance, this study uses a multiple regression model. The results of this study indicate that the variables that influence tax avoidance are leverage, company size, and profitability that affect tax avoidance. While the variables size of a public accounting firm, audit committee, institutional ownership, and sales growth show no effect on tax evasion. The leverage variable has an effect on tax avoidance because the greater the debt, the lower the taxable profit because the tax incentive for debt interest is greater. The company size variable has an effect on tax avoidance because the larger the company size, the company management efforts to try to reduce the tax burden. The variable profitability affects tax avoidance because the higher the level of company profitability, the more mature the company is in positioning tax planning which aims to reduce the amount of tax burden liabilities.